Is prolonged febrile syndrome associated with reactive thrombocytosis a possible association in the diagnosis of Takayasu’s arteritis? A case report - Victoria Birlutiu (SAGE Publishing, 2021)
Takayasu’s arteritis is a rare, systemic, inflammatory vasculitis of large blood vessels with an unknown aetiology that more frequently affects women of childbearing age with progression to stenosis, fibrosis or thrombogenesis. Clinical manifestations are associated either with inflammation of the vascular wall (including fever, myalgia, arthralgia, weight loss) or the development of aneurysms and extensive vascular lesions, which creates challenges for a differential diagnosis. This current report presents the case of a female Caucasian patient, aged 23 years, that presented herself repetitively at the hospital reporting symptoms including fever, productive cough, myalgia associated with physical effort, arthralgia, inconstant headache, weight loss and altered general condition. The patient was diagnosed with Takayasu’s arteritis in the context of a prolonged febrile syndrome associated with reactive thrombocytosis. This association results in the need to exclude multiple differential diagnoses. Nonspecific management was initiated, which included antibiotic treatment, antifungal medication, anticoagulants, steroidal anti-inflammatory drugs and correction of anaemia. The patient slowly improved. Takayasu’s arteritis in the inflammatory phase associated with a prolonged febrile syndrome and reactive thrombocytosis is a rare diagnosis of exclusion of a multitude of inflammatory diseases of large blood vessels, infectious diseases and neurofibromatosis, which requires multiple investigations for an accurate diagnosis and management.